Retroaktywna „defaszyzacja faszyzmu” w interpretacji Emilio Gentilego - Sondel-Cedarmas, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The text is devoted to the concept of “retroactive trivialization of fascism” developed at the beginning of the 21st century by an Italian historian — Emilio Gentile. According to Gentile, the phenomenon of “banalization of fascism”, inaugurated in the postwar years in neo-fascist memorialism and continued by some of the contemporary historians, consists in: 1 negation of totalitarian character of Italian fascism and presenting it as an authoritarian dictatorship of traditionalistic type; 2 challenging the existence of “positive” fascist ideology, and in 3 characterizing Mussolini’s regime as a personal “duce” dictatorship created on the basis of traditional elites. In the Gentile’s concept, fascism constituted “an Italian road to totalitarianism”, was atotalitarian experiment having its own positive ideology and forming ademonstration of new, revolutionary, and totalitarian nationalism.
Keywords: Gentile Emilio; faszyzm; interpretacje